The effect of sperm DNA fragmentation index on assisted reproductive technology outcomes and its relationship with semen parameters and lifestyle - Yang, Hongyi (Transl Androl Urol, 2019)
BACKGROUND: The sperm DNA fragmentation index (DFI) is widely regarded as a key measure for assessing male fertility, but the predictive value of the DFI for outcomes of assisted reproductive technology (ART) remains under debate. In this study, we used a large sample to analyze the effect of sperm DFI on pregnancy outcomes following ART and its relationship with oocyte fertilization and embryo development in in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). We also explore the value of sperm DNA fragmentation (SDF) and its associated factors in assessing male fertility. METHODS: The relationship between the DFI measured with the sperm chromatin structure assay (SCSA) and pregnancy outcomes following ART were retrospectively analyzed in 2,622 ART treatment cycles, of which 1,185 were intrauterine insemination (IUI) cycles, 1,221 were IVF cycles and 216 were ICSI cycles. Rates of pregnancy, early abortion, oocyte fertilization and good quality embryos from IVF and ICSI cycles were compared between the groups of low DFI (DFI ≤15%), medium DFI (15%< DFI <30%) and high DFI (DFI ≥30%). Additionally, the relationships between sperm DFI and male lifestyle variables such as age, body mass index, smoking, and alcohol consumption, as well as routine semen parameters, were analyzed. RESULTS: Clinical pregnancy rates following IUI among high, medium, and low sperm DFI groups were 12.5% (11/88), 14.3% (48/336), and 13.4% (102/761), respectively, with no statistical difference between the groups (P=0.88); however, early abortion rates among these groups were 27.3% (3/11), 14.6% (7/48), and 4.9% (5/102), respectively, and the difference was statistically significant (P=0.02). No significant differences in the rates of clinical pregnancy, early abortion, oocyte fertilization, or good quality embryos in IVF or ICSI cycles were detected among different DFI groups (P<0.05). Sperm DFI was negatively associated with sperm density, vitality and normal morphology; It was positively correlated with age, abstinence time and unhealthy lifestyles. CONCLUSIONS: As an increasingly common technique for reproductive testing, sperm DFI has proven to be very valuable in male fertility evaluation, but its significance as a predictor of pregnancy outcomes following ART requires further investigation.